A Legal Analysis of the Implementation of Law No. 22 of 2022 on Corrections - Supardi, Supardi; Putri, Hanuring Ayu Ardhani; Suniaprily, Firstnandiar Glica Aini (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study examines the implementation of Law No. 22 of 2022 on Corrections, focusing on inmate development at the Class IIA Sragen Correctional Institution. An empirical juridical method was employed using statutory and empirical approaches to assess the alignment between correctional legal norms and their practical application. Data were collected through interviews, observation, documentation, and literature review. The findings indicate that inmate development has been oriented toward social reintegration through personality and self-reliance programs. However, its implementation has not been optimal due to limitations in facilities and infrastructure, shortages of qualified personnel, overcrowding, limited community support, and ineffective administrative procedures. These findings demonstrate that inmate development has not yet been fully supported by an integrated correctional system. Accordingly, strengthening correctional policies is necessary through improving human resource capacity, enhancing facilities, simplifying administrative mechanisms, and reinforcing cross-sectoral collaboration to support effective social reintegration of inmates in accordance with the objectives of the correctional system.